Influencia del tratamiento térmico en la cristalización y rugosidad de películas delgadas de LiNbO3 depositadas por el método Spin Coating - Zirpoli, A. [UNESP] (2001)
Lithium niobate (LiNbO3) thin films with 1/1 stoichiometry were prepared by a spin-coating from polymeric precursor method. The films deposited on silicon (100) substrates, were thermally treated from 400° to 600°C for 3 hours in order to study the influence of thermal treatment on the crystallinity, microstructure, grain size and roughness. X-ray diffraction (XRD) results showed that LiNbO3 phase crystallizes at low temperature (400°C). It was observed by scanning electron microscopy (SEM) that it is possible to obtain dense thin films at temperatures around 500°C. The atomic force microscopy (AFM) results showed that the grain size and roughness are strongly influenced by the annealing temperature.